"The War at the Gates" by Shelomo ben Aharon of Poswol - Kubicki, Sebastian (2025)
The article presents—using the Karaite work "The War at the Gates" by Shelomo ben Aharon (17th/18th century; a polemic with rabbinic Judaism)—three common issues related to the analysis of Hebrew manuscripts written before the 19th century. These issues include: (1) determining the fundamental meaning of individual parts of the work; (2) analyzing the argumentative structure of the work’s narrative in relation to its biblical interpretation, which seeks to justify specific religious laws established within the religious community of the tradition/author; (3) verifying certain commonly accepted scholarly assumptions. I demonstrate how I addressed these challenges while working on the aforementioned treatise and attempt to draw generalized, practical conclusions.
Keywords: Aharon, Shelomo ben; Karaite religious law (halakha); Shelomo ben Aharon; methodological challenges; studies in Karaite literature (Hebrew texts); Karaitischer Judaismus